PENGARUH TUTOR TEMAN SEBAYA TERHADAP MINAT BELAJAR SISWA KELAS XI PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 8 KOTA JAMBI - Pratiwi Indah Sari, Maulia Widiyati, (SJEE (Scientific Journals of Economic Education), 2017)
This study aims to determine the description of respondents about peer tutors on student interest in the subjects of economy class XI IPS in SMA Negeri 8 Kota Jambi, and to determine the influence of peer tutors on student interest in the subjects of economy class XI IPS in SMA Negeri 8 Kota Jambi. Based on data analysis on the results of research that there is a significant influence between peer tutors on the interest of learning on the economic subjects of class XI SMA Negeri 8 Kota Jambi. In ANOVA, the value of F = 16.232 with α (sig) = 0.002. Because α (Sig) <0.05, then regression can be used to predict peer tutor at 95% confidence level. In coefficient the value of B constant = 68,622, states that if the peer tutor variables are ignored, the interest in learning = 68.622. Meanwhile, the variable value for peer tutor (X) is 6,292, stating that if the peer-level tutor is involved, the interest in learning increases around 6.292.Kata Kunci : Peer Friends Tutor, Interest Learning